Isolation and purification of antibacterial lipopeptides from Bacillus velezensis YA215 isolated from sea mangroves - Yu, FuTian; Shen, YuanYuan; Qin, YaLi; Pang, YiYang; Fan, HeLiang; Peng, JingJing; Pei, XiaoDong; Liu, XiaoLing (Frontiers in Nutrition, 2022)
The increasing burden and health risks of antimicrobial resistance (AMR) pose a great threat to society overall. Lipopeptides exhibit great potential as novel and safe alternatives to traditional antibiotics. In this study, the strain YA215, which was isolated from the mangrove area in Beibu Gulf, Guangxi, China, was identified as Bacillus velezensis. Then, YA215 lipopeptide extracts (YA215LE) from B. velezensis was found to exhibit a wide spectrum of antibacterial and antifungal activities. Additionally, YA215LE was identified and found to contain three groups of lipopeptides (surfactin, iturin, and fengycin). Furthermore, one separation fraction (BVYA1) with significant antibacterial activity was obtained. Additionally, liquid chromatography tandem mass spectrometry (LC-MS/MS) analysis of BVYA1 showed three molecular ion peaks ([M + H]+: m/z 980.62; 994.66; 1008.66) corresponding to conventional surfactin homologs. By MS/MS analysis, BVYA1 was identified as sufactin with the precise amino acid sequence Glu–Leu/Ile–Leu–Val–Asp–Leu–Leu/Ile and hydroxyl fatty acids with 11–13 carbons. [M + H]+ at m/z 980.62 was detected for the first time in B. velezensis, which demonstrates that the strain corresponds to a new surfactin variant. In particular, BVYA1 showed antibacterial activity with the minimum inhibitory concentration (MIC) values of 7.5–15 μg/ml. Finally, the preliminary mechanism of inhibiting E. coli treated with BVYA1 showed that BVYA1 effectively permeabilized the cytoplasmic membrane and disrupted the morphology of targeted bacterial cells. In conclusion, this study suggests that the YA215LE from B. velezensis YA215 might be a potential candidate for a bactericide.